Clash of jurisdictions, case judicial control of parliamentary decisions of the Congress of The Republic of Peru - Cáceres Arce, Jorge Luis; Cáceres Rosado, Joaquín Ignacio; del Carpio Ugarte, Cesar Alejandro (REVISTA ELECTRONICA IBEROAMERICANA, 2025)
This article examines the conflict of competence between the Congress of the Republic and the Judiciary in the Republic of Peru, with emphasis on the interference of the Judiciary in exclusive attributions of the Legislature, such as: the election of the Ombudsman, political control and the normative legislative function. The doctrine of “political questions” is explored, arguing that certain acts, due to their eminentlypolitical and representative nature, should be outside judicial control. In addition, the principles developed in the judgment handed down in file No. 00003-2022-PCC/TC and comparative international doctrine are studied. In both units of study, the importance of maintaining the separation of powers stands out, respecting the exclusive competences of each organ of the State. In conclusion, the article highlights the relevance of constitutional control to prevent institutional crises, stressing that respect for the powers of the branches of government is essential for democratic stability.
Keywords: Judicial control and review; Political questions; Parliament; Government; Constitutional Faculties; Peru